2009
DOI: 10.3354/meps07893
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences and interannual variability in occurrence of the harbour porpoise Phocoena phocoena off northwest Scotland

Abstract: The harbour porpoise Phocoena phocoena is the most common cetacean around the British Isles, but knowledge of its ecology, habitat preferences and inter-annual variability is still inadequate. Here, sightings collected by the Sea Watch Foundation during vessel surveys in West Scotland (August during the years 1993, 1994, 1996 and 1997) were critically analysed and used to construct a predictive habitat model for harbour porpoises in the Greater Minch. Generalised additive models were used to analyse relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…All models in the confidence set included depth (Table 4). Porpoises were more likely to occur in the deeper ranges (> 60 m) of the study area, with a 3-fold difference in occurrence evident See Table 1 Table 1 (Carretta et al 2001, Northridge et al 1995, Weir et al 2000, Marubini et al 2009, Embling et al 2010. Watts & Gaskin (1985) suggested that the animals may in fact be actively avoiding turbulence in shallow (<10 m) areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All models in the confidence set included depth (Table 4). Porpoises were more likely to occur in the deeper ranges (> 60 m) of the study area, with a 3-fold difference in occurrence evident See Table 1 Table 1 (Carretta et al 2001, Northridge et al 1995, Weir et al 2000, Marubini et al 2009, Embling et al 2010. Watts & Gaskin (1985) suggested that the animals may in fact be actively avoiding turbulence in shallow (<10 m) areas.…”
Section: Discussionmentioning
confidence: 99%
“…The harbour porpoise Phocoena phocoena Linnaeus 1758 is a prime example of a species for which predictive power of distribution and habitat preference has been difficult to obtain across large spatial scales (Embling 2008, Marubini et al 2009, Embling et al 2010) because both its environment and its responses to the environment are highly variable. For example, although harbour porpoises are known to eat a wide variety of prey across their entire range, their diet tends to be dominated by only 2 to 4 main prey species in any given area ).…”
Section: Abstract: Generalized Additive Models · Phocoena Phocoena ·mentioning
confidence: 99%
See 1 more Smart Citation
“…Large fl uctuations in harbor porpoise sightings observed interannually may be attributed to sampling only a portion of their effective range (e.g., Marubini et al, 2009). While a number of harbor porpoise populations found along the coastline of the eastern North Pacifi c seem to have established home ranges (Chivers et al, 2002), the extent of area used by Cook Inlet harbor porpoise is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Speckman et al (2005) found the highest densities of herring and longfi n smelt in warm waters <40 m deep, but herring peaked in clearer, more saline waters while longfi n smelt peaked in more turbid, fresher waters. Johnston et al, 2005;Marubini et al, 2009;Gilles et al, 2011). Given schooling prey occupy a range of oceanographic domains in the lower inlet, this may explain some of the interannual variability in harbor porpoise encounter rates in offshore versus nearshore areas during systematic surveys (e.g., NMFS beluga whale survey data).…”
Section: Discussionmentioning
confidence: 99%